Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1476-5381.2010.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Irbesartan treatment up‐regulates hepatic expression of PPARα and its target genes in obese Koletsky (fak/fak) rats: a link to amelioration of hypertriglyceridaemia

Abstract: BACKGROUND AND PURPOSEHypertriglyceridaemia is associated with an increased risk of cardiovascular disease. Irbesartan, a well-established angiotensin II type 1 receptor (AT1) blocker, improves hypertriglyceridaemia in rodents and humans but the underlying mechanism of action is unclear. ) or vehicle by oral gavage over 7 weeks. Adipocyte-derived hormones in plasma were measured by ELISA. Gene expression in liver and other tissues was assessed by real-time PCR and Western immunoblotting. EXPERIMENTAL APPROACH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Therefore, the mechanism by which irbesartan reduces plasma triglyceride level may depend on PPARγ activation. In the present study, PPARα was also upregulated by irbesartan and pioglitazone, as reported in previous papers (35,36). PPARα is predominantly expressed in the liver, where it has a crucial role in regulating fatty acid oxidation, and its activators, such as fibrates, are known to reduce plasma triglyceride levels (37).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Therefore, the mechanism by which irbesartan reduces plasma triglyceride level may depend on PPARγ activation. In the present study, PPARα was also upregulated by irbesartan and pioglitazone, as reported in previous papers (35,36). PPARα is predominantly expressed in the liver, where it has a crucial role in regulating fatty acid oxidation, and its activators, such as fibrates, are known to reduce plasma triglyceride levels (37).…”
Section: Discussionsupporting
confidence: 65%
“…Thus, the reduction of plasma triglyceride level in the current study in response to irbesartan treatment may be mediated by the increase in adiponectin. Nevertheless, a recent study in obese hypertensive rats reported a reduction of plasma triglyceride level by irbesartan without a concomitant increase of plasma adiponectin (35). Further studies are needed to clarify the mechanism of reduction of plasma triglyceride level by irbesartan.…”
Section: Discussionmentioning
confidence: 99%
“…Irbesartan has been reported to improve hepatic steatosis and hepatic fibrosis by activating PPARα, in NASH model FLS ob/ob mice (17). Another study also demonstrated that irbesartan upregulated PPARα in obese Koletsky (fa k /fa k ) rats and improved their metabolic disorders (18). In our model, PPARα activation may also act to improve the pathological characteristics of the MS.…”
mentioning
confidence: 82%
“…Supporting these data, HFD-induced obesity in mice was associated with increased hepatic peroxisome proliferator-activated receptor-γ, carnitine palmitoyltransferase-1, and acetyl-CoA carboxylase, and these changes were associated with decreased serum triacylglycerol. 32 Furthermore, ACE knockout mice exhibit increased wholebody energy expenditure and increased liver expression of genes involved in fatty acid oxidation, 17 supporting a direct role of Ang II in regulating fatty acid oxidation. Our study corroborate these findings once we showed that administration of Ang-(1-7) can lead to a decrease in the expression of genes related to hepaticmitochondrial fatty acid oxidation, with acetyl-CoA carboxylase and peroxisome proliferatoractivated receptor-γ.…”
Section: -13mentioning
confidence: 99%